Renal distal tubular handling of sodium in central fluid volume homoeostasis in preascitic cirrhosis. Issue 5 (1st November 1999) - Sansoè, G; Ferrari, A; Baraldi, E; Castellana, C N; De Santis, M C; Manenti, F
Abstract : BACKGROUND/AIMS: Patients with preascitic liver cirrhosis have an increased central plasma volume, and, for any given plasma aldosterone concentration, they excrete less sodium than healthy controls. A detailed study of the distribution of sodium reabsorption along the segments of the renal tubule, especially the distal one, is still lacking in preascitic cirrhosis. METHODS: Twelve patients with Child-Pugh class A cirrhosis and nine control subjects (both groups on a normosodic diet) were submitted to the following investigations: ( a ) plasma levels of active renin and aldosterone; ( b ) four hour renal clearance of lithium (an index of fluid delivery to the loop of Henle), creatinine, sodium, and potassium; ( c ) dopaminergic activity, as measured by incremental aldosterone response to intravenous metoclopramide. RESULTS: Metoclopramide induced higher incremental aldosterone responses, indicating increased dopaminergic activity in patients than controls, which is evidence of an increased central plasma volume (+30 min: 160.2 (68.8) v 83.6 (35.2) pg/ml, p<0.01; +60 min: 140.5 (80.3) v 36.8 (36.1) pg/ml, p<0.01). Patients had increased distal fractional sodium reabsorption compared with controls (26.9 (6.7)% v 12.5 (3.4)% of the filtered sodium load, p<0.05). In the patient group there was an inverse correlation between: ( a ) absolute distal sodium reabsorption and active renin ( r −0.59, p<0.05); ( b ) fractional distal sodium reabsorption and sodium excretion ( r −0.66, p<0.03). CONCLUSIONS: These data suggest that in preascitic cirrhosis the distal fractional tubular reabsorption of sodium is increased and critical in regulating both central fluid volume and sodium excretion.